ANALISIS PERAN ZAKAT SEBAGAI SOLUSI KEBIJAKAN MONETER DIMASA PANDEMI - Cintana, Arsiah Dwi (Filantropi : Jurnal Manajemen Zakat dan Wakaf, 2022)
Zakat is an expenditure of wealth that must be issued by Muslims and is given to help government programs and alleviate poverty. Therefore paying zakat can also be useful for the progress of a country. The role of zakat is as a financial controller in the country which is known as monetary policy. Because zakat is included in state income which is channeled for the welfare of the community in the economic field, such as employment opportunities, fair distribution of income and wealth, and stability of the value of money to groups who are entitled to receive it to meet needs and increase equitable economic growth. Paying zakat is very beneficial for life because it can increase one's faith in Allah SWT. In addition, zakat also participates. Zakat adalah pengeluaran harta yang wajib dikeluarkan oleh orang muslim dan diberikan membantu program pemerintah dan mengentaskan kemiskinan. Maka dari itu membayar zakat dapat berguna juga untuk kemajuan suatu negara. peran zakat adalah sebagai pengendali keuangan di dalam negara yang dikenal dengan kebijakan moneter. Karena zakat termasuk dalam pendapatan negara yang disalurkan untuk mensejahterakan masyarakat di bidang ekonomi seperti, kesempatan peluang kerja, keadilan distribusi pendapatan dan kekayaan, serta stabilitas nilai uang.kepada golongan yang berhak menerimanya untuk memenuhi kebutuhan serta meningkatkan pemerataan pertumbuhan ekonomi. Membayar zakat sangat memberi manfaat untuk kehidupan karena dapat meningkatkan iman seseorang pada Allah SWT. Selain itu, zakat juga ikut.